Analysis of Marketing Mix Implementation at Pt. Pegadaian of Malalayang Branch of City of Manado - Radlyah Hasan Jan (Tasharruf: Journal Economics and Business of Islam, 2019)
AbstractThis study aims to: (1) find out the marketing mix of gold pawn on credit realization partially, (2) find out the marketing mix of gold pawn on credit realization simultaneously, (3) find out the marketing mix of gold pawn effect on the number of customers partially and (4) find out the marketing mix of gold pawn effect on the number of customers simultaneously.The results of the multiple regression analysis show that the promotion mix variable (X1) is -0.033. It means that for every percent of enhancement in the promotion mix, it will reduce the excellence of Pegadaian by 0.033 percent. However, it does not have a significant effect, which means that the size of the promotion costs does not affect the excellence of Pegadaian. Customer satisfaction (X2) is 0.397; it shows that an increase every percent in customer satisfaction will increase the excellence of Pegadaian by 0.397 percent and significant at α of 0.05. Then the interest rate is 0.459. It shows that any percent increase in interest rate will increase the excellence of Pegadaian by 0.459 percent and significant at α of 0.0.By holding the F test, the promotion mix (X1), customer satisfaction (X2) and credit interest rates (X3) simultaneously on the excellence of Pegadaian (Y) is 0,000 < 0,05 and the calculated F value is 18,634 > F table 4,10, so that it can be concluded that the hypothesis is accepted which means there are influences of X1, X2, and X3 simultaneously on Y. The value of R Square is 0.783; it means that the influence of variables X1, X2, and X3 simultaneously on the Y variable is 78.3%. Adjusted R square is 0.620. It shows that, in this study, 62 % can be explained by the studied variables, and the rest explained by other variables outside of this study.Keywords: Analysis, Implementation, Marketing Mix